Intake of Some Biological Seeds and Root Extracts of Plants Improves Fertility and Hatchability of Turkey Eggs - Ndubuisi S. Machebe,; Simeon O. Ugwu,; C.S. Atu,; Ndofor-Foleng H. Mbunwen, (Journal of Basic & Applied Sciences, 2013)
An experiment was conducted to determine the fertility and hatchability of eggs laid by Turkey hens fed extracts of okra seed, pumpkin seed and guava root powder for 8 weeks. Twenty four, 32 weeks old turkeys (4 toms and 20 hens) were randomly selected and allotted into four treatment groups; T1 (No extract or feed supplementation); T2 (50 ml okra seeds extracts/ litre of water); T3 (50 ml guava root extract/ litre of water) and T4 (50 g pumpkin seed powder/kg of feed). Turkey hens were subjected to artificial insemination and eggs laid in the period were collected and determined for fertility and hatchability. Total and weekly egg production of hens was higher (P < 0.05) in T2 and T4 groups of birds. The number of fertile eggs, early, middle and late dead embryo was better (P < 0.05) for the same groups of birds compared to other treatments. Egg hatchability percentage of hens in T2 and T4 groups were markedly improved and higher (P < 0.05) than those in T1 and T3 groups. Fertility and hatchability of eggs in T1 and T3 were similar (P > 0.05). The findings concluded that feeding okra and pumpkin seed extracts to breeder turkey hens can improves the fertility and hatchability of the eggs.